Cancer ablation by high intensity focused ultrasound - Muhammad Luqman Abdul Halim (2018)
The calculation of pressure fields using High Intensity Focused Ultrasound (HIFU) spans various methods and approach. This report will conduct simulations and calculation of pressure fields using a numerically quicker method called Angular Spectrum Approach (ASA) and aims to compare it with current traditional methods such as the Rayleigh-Sommerfeld Integral. The method to achieve this is to employ a MATLAB toolbox developed by University of Michigan researchers known as FOCUS. Apart from comparing these two methods, we will also investigate the effects of attenuation, diffraction and dispersion of HIFU beam in non-homogenous media such as the skin, fat, muscle and liver. We will also discuss and investigate the pressure intensity of these affected areas.